PERSEPSI MAHASISWA UNIVERSITAS DHARMA ANDALAS TERHADAP TAYANGAN KEKERASAN DI TELEVISI - Diego Diego; Indria Flowerina (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
Television that has the greatest potential for our lives. This happens because the power of audiovisual television that touches the mental aspects of viewers and television media has become a reflection of the culture of spectacle. One of the issues is how much violent content is found on television. Students as one of the television audience segments have different perceptions than children. This study looks at how perceptions of violence among students using interview data collection techniques. The method used is qualitative. From the results of the research, there were negative perceptions about violence on television, but they still watched it on soap operas and films. The government must be able to exercise more control and action in order to reduce the negative impact on children.